CREATION AND USAGE METHOD OF SOFTWARE TOOLS AIMED AT DEVELOPING STUDENTS' ALGORITHMIC THINKING IN PROGRAMMING (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article highlights the advantages of programming languages and the challenges of developing students' algorithmic thinking related to programming. Additionally, this article presents the method of creating software tools aimed at developing students' algorithmic thinking in programming, along with suggestions and recommendations for their usage.